KEVARIASIAN KEVARIASIAN DALAM TEKS EKSPLANASI KARYA SIWA SMP: VARIASI DALAM PEMBUKAAN KALIMAT, POLA KALIMAT, DAN JENIS KALIMAT - WIDYA FATKHAN; Dawud; Susanto, Gatut (Literasi: Jurnal Ilmiah Pendidikan Bahasa, Sastra Indonesia dan Daerah, 2024)
Sentences have an important role in spoken and written language activities. Units of thought, idea, or message in a sentence must be able to be conveyed clearly by a speaker and writer. The ideas in explanatory text are no exception. This explanation is packaged, among other things, in the form of definitions, arguments, clarifications, classifications, interpretations and constructions. The use of effective sentences should be applied by class VIII junior high school students in writing explanatory texts. If students can apply the rules of effective sentences, then the written explanatory text can be easily understood by readers and does not give rise to multiple interpretations. This research uses a qualitative approach. The data in this research are in the form of effective and ineffective sentences contained in the explanatory text written by students of SMPN 1 Turen class 8 based on the aspects of variation, parallelism, economy and completeness. The data source for this research is a collection of explanatory texts by students of SMPN 1 Turen class 8 obtained from teachers who teach Indonesian language subjects. Based on variation, variations were found in sentence opening. Each sentence begins with a noun, adverb of time, verb, and conjunction. Sentences with different types of nouns, adverbs of time, verbs and conjunctions were found. Apart from variations in openings, variations in sentence patterns were also found consisting of subject-predicate-complement (S-P-Pel), predicate-subject-object (P-S-O), object-subject-predicate (O-S-P), subject-adverb-predicate (S-K-P) patterns. ), and adverb-subject-predicate (K-S-P).